Studi Pengembangan Perangkat Pembelajaran Berbasis Implementasi Model ADDIE Di Mataram - Barinta Nur Respasari; Fahmi Firdaus; Gunawan Gunawan; Susilawati Susilawati (Indonesian Publication Center, 2023)
This study aims to identify the process and results of the application of the ADDIE model in the development of learning devices in Mataram and evaluate its impact on the quality of learning. The ADDIE model consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. This study uses a literature study method to examine the concepts and theories used. The results of the study indicate that the ADDIE model is effective in improving student understanding and engagement. These findings are expected to provide practical guidance for educators and developers in optimizing the use of the ADDIE model in various educational contexts.